2021
DOI: 10.1007/s11665-021-06389-6
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Wear Resistance Performance of CuAl8Fe3 Single-Phase Aluminum Bronze via Slide Diamond Burnishing

Abstract: Single-phase CuAl8Fe3 aluminum bronze is preferred material for many applications requiring good strength and high corrosion and wear resistance. Due to its lower aluminum content (below 8.5%), this alloy cannot be subjected to heat treatment. The effect of diamond burnishing (DB) on wear resistance performance of this bronze was studied via wear tests under boundary lubrication and dry friction conditions. Three groups of specimens were tested, each subjected to different finishing process: fine turning, DB w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…DB was carried out after the HTs. The schematic of the DB set-up and the methodology were explained in our previous studies [39,41,42].…”
Section: Specimen Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…DB was carried out after the HTs. The schematic of the DB set-up and the methodology were explained in our previous studies [39,41,42].…”
Section: Specimen Treatmentmentioning
confidence: 99%
“…The effect of DB on the sliding wear resistance of IABs in the as-received state for two friction modes (boundary lubrication and dry friction) was studied in [42,47]. DB significantly improves the wear resistance of IABs.…”
Section: Sliding Wear Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximov et al indicated that the tip radius and the fb had the strongest effects on the residual stresses for the burnished 41Cr4 steel [5]. Duncheva et al emphasized that the diamond burnished surface was significantly improved in terms of wear resistance, as compared to the fine turning, while the geometrical characteristics had significant impacts on the lubrication of the burnished surface [6]. Duncheva et al stated that the surface characteristics (hardness and texture) were effectively enhanced with the support of internal diamond burnishing [7].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the favourable properties of the surface layer of slide-burnished parts, there is increased fatigue strength [51,52], improved corrosion resistance [55], and abrasion resistance [56]. Slide burnishing also works well for finishing materials that cannot be subjected to heat treatment [57]. It was also found that the geometrical characteristics of surface texture are significant under boundary lubrication friction, while the physical and mechanical characteristics of the surface layer are important under dry friction conditions.…”
Section: Introductionmentioning
confidence: 99%